SAS in practice - Saraogi, Ekta (Packt, 2019)
"This course will help you become a confident and proficient data analyst and SAS programmer by giving you the hands-on knowledge and in-depth understanding of the SAS programming suite and how to utilize it effectively. Additionally, it will help you master different techniques in SAS to manipulate your data. You'll learn how to work with SQL queries and generate effective data reports. Moreover, this course will provide all the content you're looking for to prepare for the SAS Base certification exam. By the end of this course, you'll have a thorough understanding of the fundamental SAS concepts, along with rich hands-on experience of the SAS suite."--Resource description page